ANALYSIS OF PATIENT SAFETY CULTURE ON PATIENT SATISFACTION AND ITS IMPLICATIONS ON THE QUALITY OF HEALTHCARE SERVICES - Nugraha, Agung; Rahmiyati, Ayu Laili; Yuliaty, Farida; Kosasih, Kosasih (HEARTY, 2026)
This study aims to analyze patient safety, patient satisfaction, and the quality of healthcare services at, Cirebon. This study used a quantitative approach. The sample size was 100 respondents. Data analysis used descriptive analysis and verification analysis using path analysis. The descriptive analysis of patient safety, patient satisfaction, and the quality of healthcare services provided good ratings, however, several shortcomings were identified that require attention and improvement. Meanwhile, the results of the verification research, the path analysis model shows that the path coefficient value between variables is positive and the path coefficient value of the direct influence is greater than the indirect influence (76.3%>71.5%), meaning that the patient satisfaction variable as an intervening variable is able to mediate the relationship between patient safety and the quality of health services. The correlation coefficient value of 0.941 indicates a strong relationship between variables and the determination coefficient value (R2) of 88.3%, indicating that the variation in the influence of patient safety variables and variables on patient satisfaction of the quality of health services variable is quite large. The statistical hypothesis results for the t-test (partial) indicate that the patient safety variable has a positive effect on patient satisfaction, as the calculated t-value > tα (12.75 > 1.98). The patient safety variable has a positive and significant effect on the quality of healthcare services, as the calculated t-value > tα (17.697 > 1.98). The patient satisfaction variable directly has a positive and significant effect on the quality of healthcare services, as the calculated t-value > tα (20.803 > 1.98). The patient safety variable indirectly has a positive effect on the quality of healthcare services through the patient satisfaction variable, as the calculated t-value > tα (10.874 > 1.98). The overall results of the study indicate the implications of the patient safety and patient satisfaction variables for the quality of healthcare services.